Efektivitas Pesan Gambar Kemasan Rokok Terhadap Motivasi Berhenti Merokok Mahasiswa Ikom Untidar: indonesia - Adam Tri Sunarto; Alif Wahyu Romadhon; Fadian Firzal Akbar Ramadhani (CV. ITTC INDONESIA, 2022)
The study was conducted to determine the effectiveness of picture messages on cigarette packages on motivation to stop smoking in Tidar University Communication Studies students. The purpose of this study was to find out how effective the picture messages on cigarette packages were on smoking cessation motivation among Tidar University Communication Studies students. The research was conducted using descriptive quantitative methods to describe the statistical test results of the data that had been collected. The collection of samples was obtained from a population with non-probability sampling purposive sampling with a total of 61 respondents. Then the test used is the correlation test Pearson Correlation Test which aims to find out the comparison of r count with r table. with the test results, namely based on the results of the significance of the correlation test conducted stating that the significance of variable X to variable Y is 0.000, which is 0.000 <0.05. Based on t count > t table (4.8 > 2.001), it can be said that H0 is rejected, this indicates that there is a significant influence between warning images on cigarette packs on motivation to stop smoking in University Communication Studies students class of 2020. The magnitude of the impact the use of BTS as a Brand Ambassador is 85.1%. The conclusion is that the effectiveness of picture messages on cigarette packages on motivation to stop smoking in Communication Studies students at Tidar University has a magnitude of influence of 53.3%.